Health aspects of calcium in drinking water - (:unkn) unknown (Royal Society of Chemistry, 2016)
Drinking water has a great importance for human health. Therefore, the content of drinking water has been the subject of many studies for years. The hardness of drinking water, determined by the calcium and magnesium content, is in particular very important for human health. The hardness of water varies significantly in different world regions, which may lead to some different physiological effects. This chapter reviews the effects of the hardness of the drinking water in particular the calcium content on health aspects. However, the studies conducted about the hardness of drinking water mainly focused on the magnesium content. Therefore focusing more on calcium some remarkable points were also indicated about magnesium. © 2016 The Royal Society of Chemistry.